A family of dynein genes in Drosophila melanogaster. - Rasmusson, K (1994)
We report the identification and initial characterization of seven Drosophila dynein heavy chain genes. Each gene is single copy and maps to a unique genomic location. Sequence analysis of partial clones reveals that each encodes a highly conserved portion of the putative dynein hydrolytic ATP-binding site in dyneins that includes a consensus phosphate-binding (P-loop) motif. One of the clones is derived from a Drosophila cytoplasmic dynein heavy chain gene, Dhc64C, that shows extensive amino acid identity to cytoplasmic dynein isoforms from other organisms. Two other Drosophila dynein clones are 85 and 90% identical at the amino acid level to the corresponding region of the beta heavy chain of sea urchin axonemal dynein. Probes for all seven of the dynein-related sequences hybridize to transcripts that are of the appropriate size, approximately 14 kilobases, to encode the characteristic high molecular weight dynein heavy chain polypeptides. The Dhc64C transcript is readily detected in RNA from ovaries, embryos, and testes. Transcripts from five of the six remaining genes are also detected in much lesser amounts in tissues other than testes. All but one of the dynein transcripts are expressed at comparable levels in testes suggesting their participation in flagellar axoneme assembly and motility.